Unraveling Tobacco Tax Evasion in Bangladesh: Evasion Tactics and Prevention Challenges - Shah, A.M.M. Mubassher; Hasan, Adila Reza; Tamrin, Samantha (CV. Literasi Indonesia, 2025)
Despite having a high tax rate, tobacco products in Bangladesh are purchasable at lower prices due to tax evasion and avoidance compared to the rest of the world. Therefore, this study intends to explore the ways of tobacco tax evasion and challenges within the current tax system to prevent tax evasion in Bangladesh. A qualitative approach has been adopted, involving 30 in-depth interviews with retailers and 10 key informant interviews with key stakeholders. While conducting IDIs, tobacco products were also observed to identify tax-evaded products. Secondary data was gathered from relevant reports and journal articles. These were analyzed employing a thematic analysis approach. The study reveals that tax evasion in Bangladesh primarily occurs through the use of counterfeit tax stamps, illicit trade, fraudulent financial reporting, and illegal production. It also highlights the misuse of the tax tier system and the weak enforcement and monitoring system as key challenges of the current tax system in Bangladesh. These findings underscore the importance of a centralized digital monitoring system using tools such as digital tax stamps or QR codes and scanners to detect tax information to enhance tobacco tax compliance and prevent tax evasion in Bangladesh.